Diaphragm for hydrogen production through alkaline water electrolysis and preparation method thereof

By adopting a combined structure of a fiber base layer and a coating layer in the alkaline water electrolytic hydrogen production membrane, the pore-like connection points are used to enhance the bonding fastness, the existing membrane has high resistance and poor gas isolation, and the production of hydrogen with lower energy consumption and higher purity is achieved.

CN119877030APending Publication Date: 2025-04-25SHANGHAI QIANFENG TECH TEXTILES CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510054840.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-14
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing alkaline water electrolytic hydrogen-producing membranes have problems such as high resistance and poor gas isolation, which leads to high energy consumption of the electrolytic cell and low gas purity.

Method used

A diaphragm consisting of a fiber substrate layer and a coating layer located on both sides of the fiber substrate layer is used. A plurality of through hole-like connection points are provided on the fiber substrate layer, and the coating layer is connected into one through these connection points to improve the bonding fastness and service life of the diaphragm.

Benefits of technology

It significantly improves the service life and toughness of the diaphragm, reduces the energy consumption of the electrolytic cell, and improves the gas production purity.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to a diaphragm for hydrogen production through alkaline water electrolysis and a preparation method of the diaphragm. The diaphragm for hydrogen production through alkaline water electrolysis comprises a fiber base material layer and coating layers located on the two sides of the fiber base material layer. A plurality of through hole-shaped connecting points are arranged on the fiber base material layer, and the coating layers on the two sides of the fiber base material layer are connected into a whole through the hole-shaped connecting points; during preparation, a non-woven fabric structure base material is prepared through a non-woven fabric technology and punched, then a high-molecular polymer, a pore-foaming agent and hydrophilic inorganic particles are added, or a resin strengthening and toughening agent is further added to obtain a coating solution, then the two sides of the fiber base material layer are coated with the coating solution at the same time, and finally the fiber base material layer is put into water to be subjected to phase conversion. And curing and cleaning to obtain the diaphragm for hydrogen production by alkaline water electrolysis. The preparation method disclosed by the invention is simple, the prepared product has the characteristic of use durability, the coating is not easy to fall off, and the coating is suitable for an electrolytic cell to operate under a high-pressure working condition during use.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of electrolytic diaphragms and relates to a diaphragm for producing hydrogen by electrolysis of alkaline water and a preparation method thereof. Background Art

[0002] The electrolyzer for hydrogen production by water electrolysis is a device that uses the method of electrolyzing water to produce hydrogen. The current mainstream hydrogen production methods include alkaline water electrolysis, proton exchange membrane water electrolysis, high-temperature solid oxide electrolysis, and anion exchange membrane water electrolysis. Among them, alkaline water electrolysis is the most mature and commercialized hydrogen production method. The diaphragm is the most important component in the alkaline water electrolysis hydrogen production equipment. Its main function is to separate the hydrogen and oxygen gases produced on the anode and cathode sides of the electrolyzer to prevent the hydrogen and oxygen gases from mixing and exploding. At the same time, the diaphragm must also ensure the smooth passage of ions to reduce the energy consumption of electrolysis.

[0003] At present, the mainstream diaphragm of alkaline electrolyzer is polyphenylene sulfide fabric diaphragm, but the fabric diaphragm has problems such as high resistance and poor gas barrier, resulting in high energy consumption of electrolyzer and low purity of gas production. Therefore, those skilled in the art have been seeking low energy consumption and high purity diaphragm materials.

[0004] Patent CN110869538B discloses a reinforced diaphragm for alkaline hydrolysis, which is a composite diaphragm with a sandwich structure formed by coating a mixed slurry of inorganic particles and resin on both sides of a monofilament mesh such as PPS and PS. The inorganic particles are mainly nanoparticles of zirconium oxide or other similar properties. The oxygen ions in zirconium oxide form hydrogen bonds with water in the electrolyte, which is the main substance to improve the hydrophilicity of the composite diaphragm. The resin can be a material such as polysulfone, polyethersulfone, polyphenylsulfone, etc., and its main function is to bond the nanoparticles of zirconium oxide to form a film. However, the substrate composed of monofilaments such as PPS and PS has a small specific surface area, which limits the bonding area between the slurry and the substrate, making the slurry easy to fall off when subjected to external force, resulting in the inability to block the gas generated on the positive and negative sides of the electrolytic cell, and poor durability in use.

[0005] Therefore, it is of great significance to study a diaphragm for hydrogen production by alkaline water electrolysis and a preparation method thereof to solve the problems existing in the prior art. Summary of the invention

[0006] The purpose of the present invention is to solve the problems existing in the prior art and to provide a diaphragm for producing hydrogen by electrolysis of alkaline water and a preparation method thereof.

[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0008] A diaphragm for producing hydrogen by alkaline water electrolysis comprises a fiber substrate layer and coating layers located on both sides of the fiber substrate layer; a plurality of through-hole connection points are arranged on the fiber substrate layer, and the coating layers on both sides of the fiber substrate layer are connected into one body through the hole connection points.

[0009] The fiber substrate layer contains multiple porous connection points, through which the coating layers on both sides can be connected into one. In this way, a rivet-like connection can be formed between the coatings on both sides and penetrates the substrate. There is an interaction force between the left and right coatings and the middle substrate layer, which can greatly improve the service life of the diaphragm.

[0010] As the preferred technical solution:

[0011] As described above, in a diaphragm for producing hydrogen by alkaline water electrolysis, the fiber substrate layer is a non-woven fabric structure, which can be any one of papermaking non-woven fabric, needle-punched non-woven fabric, spunlace non-woven fabric, spunbond non-woven fabric and meltblown non-woven fabric. Considering the high specific surface area, high fluffiness and pore size uniformity of the substrate layer, the intermediate fiber substrate layer of the present invention is preferably papermaking non-woven fabric or spunlace non-woven fabric, more preferably spunlace non-woven fabric. The fiber substrate layer is composed of short fibers with a length of 10 to 76 mm, and the diameter of the short fibers is 0.1 to 20 μm.

[0012] If the fiber substrate layer is composed of non-short fiber filaments, the specific surface area of ​​the filaments is small. Using it as a diaphragm substrate can ensure the strength of the diaphragm, but it cannot provide enough surface area to combine with the resin slurry, resulting in low bonding strength between the substrate layer and the resin layer. Compared with continuous filaments, if the substrate layer uses short fibers with a fixed length and a small fiber diameter, the bonding strength between the substrate layer and the resin layer can be greatly improved, and it is more suitable for use in an environment under long-term external force. In addition, in order to ensure excellent bonding strength while having excellent processability, the length of the short fibers must be controlled between 10mm and 76mm. If the length of the short fibers is less than 10mm, the fibers that are too short cannot be bonded to each other, and the strength of the substrate layer cannot be guaranteed. If the length of the short fibers is higher than 76mm, the bonding force between the fibers that are too long is too large, and the fibers are difficult to comb and spread, and the processability cannot be guaranteed. Taking into account the processability of the fiber substrate layer and the long-term durability and toughness of the diaphragm for producing hydrogen by alkaline water electrolysis, the fiber length of the fiber substrate layer in the diaphragm for producing hydrogen by alkaline water electrolysis of the present invention is preferably 30 to 61 mm.

[0013] The diameter of the short fibers needs to be controlled at 0.1 to 20 μm. If the diameter of the short fibers is lower than 0.1 μm, the cohesion between the overly fine fibers is too large, and the fibers are easily entangled with each other, making it difficult to comb and process, and the processability cannot be guaranteed. However, if the diameter of the short fibers is higher than 20 μm, the fiber specific surface area is too small, the bonding area between the slurry resin and the substrate is small, the bonding force is insufficient, and the slurry resin is easily detached by external forces. Considering the processability of the fiber substrate layer and the long-term durability and toughness of the diaphragm for hydrogen production by alkaline water electrolysis, the fiber diameter of the fiber substrate layer in the diaphragm for hydrogen production by alkaline water electrolysis of the present invention is preferably 8 to 15 μm.

[0014] As described above, in a diaphragm for producing hydrogen by alkaline water electrolysis, the fibers in the fiber substrate layer are polyphenylene sulfide sulfone fibers or mixed fibers of polyphenylene sulfide sulfone fibers and other fibers, and the other fibers are one or more of polyphenylene sulfide fibers, polytetrafluoroethylene fibers, polypropylene fibers, polyethylene fibers, polyetheretherketone fibers and cotton fibers.

[0015] In a diaphragm for hydrogen production by alkaline water electrolysis as described above, the area of ​​the porous connection points on the fiber substrate layer accounts for 30 to 90% of the total area of ​​the fiber substrate layer. If the area of ​​the porous connection points accounts for less than 30% of the total area of ​​the fiber substrate layer, the area of ​​the connection points is too small, the bonding force between the left and right coating layers is insufficient, and there is a risk of the coating falling off when subjected to external force. If the area of ​​the connection points accounts for more than 90% of the area of ​​the substrate layer, the bonding area between the coating layers on both sides and the substrate layer is too small, the bonding force is insufficient, and there is also a risk of the coating falling off. Secondly, if the area of ​​the connection points is too large, the opening area in the substrate layer is too large, the strength of the substrate decreases, and the service life of the diaphragm will be greatly reduced. Taking into account the mutual bonding strength between the coating layers on both sides and the substrate layer and the strength of the substrate layer, the area of ​​the substrate layer connection points of the present invention preferably accounts for 50% to 80% of the total area of ​​the fiber substrate layer.

[0016] In the above-mentioned diaphragm for producing hydrogen by alkaline water electrolysis, the area of ​​a single hole-shaped connection point is 0.5 to 4 mm 2 ; If the area of ​​a single hole connection point is less than 0.5mm 2 The connection channel of the resin on both sides is too small, and it is difficult for the resin on one side to combine with the resin on the other side through the connection point. The bonding strength between the two sides of the resin decreases, and the service life of the diaphragm is reduced. If the area of ​​a single hole connection point is higher than 4mm 2, then the bonding area between the coating layer and the substrate layer on both sides is too small, the bonding force is insufficient, and there is also a risk of coating falling off; secondly, the area of ​​the connection point is too large, and the opening area in the substrate layer is too large, which will cause the strength of the substrate to decrease and the service life of the diaphragm to be greatly reduced. All porous connection points are evenly distributed on the fiber substrate, and the distance between any adjacent porous connection points is greater than 0.2mm; if the connection points are unevenly distributed in the fiber substrate, the bonding force between the left and right resins and the middle substrate layer in different areas of the diaphragm will be deviated and uneven. In the area with insufficient bonding force, the resin coating will fall off first, causing the diaphragm to fail. In addition, if the distance between any adjacent connection points is less than 0.2mm, it will cause a significant decrease in the strength of the substrate between adjacent connection points, resulting in insufficient strength of the diaphragm and affecting the service life of the diaphragm.

[0017] In the above-mentioned diaphragm for producing hydrogen by electrolysis of alkaline water, the cross-sectional shape of the hole-shaped connection point is one or more of a circular, square, angular and star-shaped. Considering that the fiber substrate layer still has a high strength after the hole is opened, the cross-sectional shape of the connection point is preferably a circular, square and angular shape, and a circular structure is more preferred.

[0018] The diaphragm for producing hydrogen by electrolysis of alkaline water as described above is placed in a NaOH solution at a constant temperature of 120° C. and a mass concentration of 30% for one month, and the weight loss of the diaphragm for producing hydrogen by electrolysis of alkaline water does not exceed 0.5%;

[0019] A peeling test was performed on the diaphragm for producing hydrogen by electrolysis of alkaline water and the bonding material. The weight loss of the diaphragm for producing hydrogen by electrolysis of alkaline water did not exceed 1% before and after the peeling test.

[0020] The present invention also provides a method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis as described in any one of the above items, comprising the following steps:

[0021] (1) Using polyphenylene sulfide sulfone fiber or a mixed fiber of polyphenylene sulfide sulfone fiber and other fibers as raw materials, a non-woven fabric structure substrate is prepared by a papermaking non-woven fabric process, a needle-punched non-woven fabric process, a spunlace non-woven fabric process, a spunbond non-woven fabric process or a melt-blown non-woven fabric process;

[0022] (2) punching the non-woven fabric structure substrate in step (1) to obtain a fiber substrate layer containing hole-shaped connection points;

[0023] (3) adding a high molecular weight polymer to an organic solvent and stirring until the high molecular weight polymer is completely dissolved to obtain a high molecular weight polymer solution;

[0024] (4) adding a porogen and hydrophilic inorganic particles to the high molecular polymer solution obtained in step (3), or further adding a resin toughening agent, and stirring and dispersing the mixture to obtain a coating solution;

[0025] (5) using a slit extrusion scraper device or a double-sided comma scraper device to simultaneously apply the coating solution to both sides of the fiber substrate layer, so that the coating can be evenly attached to both sides of the fiber substrate layer and the coatings on both sides can be connected into one through the hole-shaped connection points of the substrate layer;

[0026] (6) The system obtained in step (5) with the coating solution coated on both sides of the fiber substrate layer is put into water for phase inversion, and after solidification, it is washed to obtain a diaphragm for hydrogen production by alkaline water electrolysis.

[0027] In the method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis as described above, the organic solvent in step (3) is one or more of NMP (N-methylpyrrolidone), NEP (N-ethylpyrrolidone), DMAC (N,N-dimethylacetamide) and DMF (N,N-dimethylformamide), and the high molecular polymer is one or more of polysulfone, polyethersulfone and polyphenylsulfone;

[0028] In step (4), the porogen is one or more of PVP (polyvinyl pyrrolidone), polyethylene glycol, ethanol and n-butanol, the hydrophilic inorganic particles are one or more of zirconium oxide, aluminum oxide, magnesium oxide, yttrium oxide, cerium oxide and titanium oxide, and the resin toughening agent is polystyrene or polybutadiene.

[0029] In the method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis as described above, in the coating solution, the mass proportion of organic solvent is 30-70%, the mass proportion of high molecular polymer is 8-30%, the mass proportion of hydrophilic inorganic particles is 20-60%, the mass proportion of resin toughening agent is 0-2%, and the mass proportion of porogen is 1-15%.

[0030] If the mass proportion of organic solvent is higher than 70%, the content of resin and inorganic particles in the coating solution will be too low, the strength of the diaphragm and the ion permeability during use will decrease, the durability of use will decrease, the performance will decrease, and too much solvent will cause a large amount of waste liquid discharge problems, increasing the production cost of the product. If the mass proportion of organic solvent is lower than 30%, the viscosity of the coating solution will be too high, the fluidity of the coating solution will decrease, and it will not be possible to extrude and coat smoothly. Considering the fluidity of the coating solution, the strength of the diaphragm and the excellent performance, the solvent content in the coating solution of the present invention is preferably 40-50%.

[0031] If the mass proportion of high molecular weight polymer is less than 8%, then the resin content in the coating solution is too low. When the resin content is too low, the bonding strength between the resin layer and the fiber layer is greatly reduced. After long-term use of the electrolytic cell, the resin layer is easily separated from the fiber layer, and the electrolytic diaphragm fails. In addition, if the resin content is too low, the hydrophilic inorganic particles in the resin layer cannot be fully wrapped by the resin and are easily precipitated from the resin layer, resulting in a decrease in the hydrophilicity of the diaphragm for hydrogen production by alkaline water electrolysis, an increase in resistance, and failure of the diaphragm for hydrogen production by alkaline water electrolysis. If the mass proportion of high molecular weight polymer in the casting system is higher than 30%, then the solvent content in the casting system will be greatly reduced, the resin cannot be fully dissolved by the solvent, and there will be resin particles in the casting system that cannot be completely dissolved, which will cause the bonding strength between the resin layer and the fiber layer to decrease. In addition, the presence of resin particles during the coating of the film liquid can easily cause scratches on the coating, resulting in a decrease in the strength of the diaphragm for hydrogen production by alkaline water electrolysis and a significant decrease in service life. Taking into account the strength of the diaphragm for producing hydrogen by alkaline water electrolysis and the sufficient solubility of the resin, the mass proportion of the high molecular weight polymer of the diaphragm for producing hydrogen by alkaline water electrolysis of the present invention is preferably 10% to 20%.

[0032] If the mass proportion of hydrophilic inorganic particles is less than 20%, the content of hydrophilic inorganic particles is small, the permeability of the diaphragm for hydrogen production by alkaline water electrolysis to the electrolyte is poor, the ion permeability is reduced, and the diaphragm resistance is greatly increased. If the mass proportion of hydrophilic inorganic particles is higher than 60%, the content of hydrophilic inorganic particles is too much, on the one hand, the viscosity of the membrane liquid is too high, it is difficult to be scraped, and the productivity is poor. On the other hand, too many inorganic particles make it difficult to be effectively adhered to the resin, and the inorganic particles are easy to fall off, which greatly reduces the service life of the diaphragm. Considering the ion permeability of the diaphragm and the adhesion of the hydrophilic inorganic particles, the mass proportion of hydrophilic inorganic particles in the coating solution of the present invention is preferably 40% to 50%.

[0033] If the mass proportion of the resin toughener is higher than 2%, it will not significantly improve the reinforcing effect of the resin. Instead, it will cause the content of other components to decrease, resulting in a decrease in the performance of the diaphragm for hydrogen production by alkaline water electrolysis.

[0034] If the mass proportion of the porogen is less than 1%, it is easy to cause the porosity of the diaphragm for hydrogen production by alkaline water electrolysis to decrease, the ion permeability to decrease, and the diaphragm resistance to increase. If the mass proportion of the porogen is higher than 15%, the voids in the diaphragm for hydrogen production by alkaline water electrolysis are too large. The presence of excessive voids easily causes the toughness of the diaphragm to decrease and the brittleness to increase. When the diaphragm for hydrogen production by alkaline water electrolysis is subjected to air bubbles and electrolyte flushing, the diaphragm for hydrogen production by alkaline water electrolysis is prone to cracking, resulting in a decrease in the service life of the diaphragm. Considering the ion permeability of the electrolytic diaphragm and the strength of the diaphragm, the mass proportion of the porogen in the coating solution of the present invention is preferably 3% to 6%.

[0035] Beneficial effects:

[0036] (1) Compared with the existing composite diaphragms of polyphenylene sulfide monofilament support mesh, the use of the polyphenylene sulfide sulfone short fiber substrate layer of the present invention can greatly increase the bonding area between the coating layer and the substrate layer, and can also ensure that the coating is evenly distributed in the substrate layer. Even if the resin coating is used for a long time, it is not easy to separate and peel off, and has the characteristics of long-term durability. In addition, the polyphenylene sulfide sulfone short fibers in the substrate layer are entangled with each other through a non-woven fabric process, ensuring that the diaphragm substrate layer has a high strength, thereby providing sufficient strong support for the coating layer, and the coating layer is not easy to crack;

[0037] (2) The present invention provides a method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis. The polysulfone resin has excellent high temperature resistance and concentrated alkali resistance. The presence of hydrophilic inorganic particles can increase the permeability of the electrolyte in the electrolytic diaphragm, thereby ensuring that ions can pass through the diaphragm quickly, reducing the internal resistance of the diaphragm and improving the electrolysis efficiency. DETAILED DESCRIPTION

[0038] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0039] The performance index testing method of the present invention is as follows:

[0040] Peel test: tested according to GB / T 2792-2014; peel speed is 5.0±0.2mm / s, peel length is 50mm.

[0041] Sources of some substances of the present invention:

[0042] Polypropylene fiber: Manufacturer: Hubei Botao Synthetic Fiber Co., Ltd.

[0043] Polyethylene fiber: Manufacturer: Hunan Zhongtai Special Equipment Co., Ltd.

[0044] Polyetheretherketone fiber: Changzhou Chuangying New Material Technology Co., Ltd., PEEK fiber / diameter 0.1mm.

[0045] Polyphenylsulfone: Manufacturer: BASF; Brand: P 3010NATURAL.

[0046] Polysulfone: Manufacturer: Solvay Investment Co., Ltd., Brand: P-1700LCD;

[0047] Polyethersulfone: Manufacturer: Solvay Investment Co., Ltd., Brand: PESU 3000P;

[0048] Polyphenylene sulfide fiber: Manufacturer: Toray International Trading (China) Co., Ltd., Brand: 1.5D*51mm;

[0049] PVP: Manufacturer: Shanghai Qifuqing Material Technology Co., Ltd., Brand: PVPK30;

[0050] Polyacrylamide: Manufacturer: Anhui Tianrun Chemical Industry Co., Ltd., brand: ZF1616;

[0051] Zirconia: Manufacturer: Daiichi Rare Element Chemical Co., Ltd., particle size: 0.07-0.27 μm;

[0052] Alumina: Manufacturer: Xuancheng Jingrui New Materials Co., Ltd., particle size: 0.04-0.06 μm;

[0053] Polystyrene: Manufacturer: Ningbo Changhong Polymer Technology Co., Ltd., brand: CH1320;

[0054] Polybutadiene: Manufacturer: Zhenjiang Chimei Chemical Co., Ltd., Brand: PH-55Y;

[0055] Polyethylene glycol: Manufacturer: Hai'an Guoli Chemical Co., Ltd., brand: PEG1500.

[0056] The invention adopts a normal pressure anhydrous Na2S method to prepare polyphenylene sulfide sulfone fiber: under normal pressure, 4,4'-dichlorodiphenyl sulfone (DCDPS) and anhydrous Na2S with a mass ratio of 1:1.2 are used as monomers for polymerization, hexamethylphosphoric triamide (HMPA) and dimethylacetamide (DMAC) with a volume ratio of 1:1 are used as solvents, sodium benzoate and nitro-p-dichlorobenzene are used as catalysts and auxiliary agents respectively, and the reaction is carried out for 6 hours; wherein the total volume ratio of sodium benzoate and nitro-p-dichlorobenzene to the solvent is 1:3, the volume ratio of sodium benzoate and nitro-p-dichlorobenzene is 1:1, and the monomer concentration of 4,4'-dichlorodiphenyl sulfone (DCDPS) in the mixed solution is 0.4 mol / L. After the polyphenylene sulfide sulfone resin is obtained, the polyphenylene sulfide sulfone fiber is obtained by spinning.

[0057] Example 1

[0058] A method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis, the specific steps are as follows:

[0059] (1) Preparation of raw materials:

[0060] Polyphenylene sulfide sulfone fiber;

[0061] Organic solvent: NMP;

[0062] High molecular weight polymer: polysulfone;

[0063] Porogen: PVP;

[0064] Hydrophilic inorganic particles: zirconium oxide;

[0065] Resin toughener: polybutadiene;

[0066] (2) using polyphenylene sulfide sulfone fiber as a raw material, a non-woven fabric structure substrate is prepared by a spunlace non-woven fabric process, wherein the non-woven fabric structure substrate is composed of short fibers with a length of 51 mm and a diameter of 12 μm;

[0067] (3) punching the non-woven fabric substrate in step (2) to obtain a fiber substrate layer;

[0068] (4) adding a high molecular weight polymer to an organic solvent and stirring until the high molecular weight polymer is completely dissolved to obtain a high molecular weight polymer solution;

[0069] (5) adding a porogen, hydrophilic inorganic particles and a resin toughening agent to the high molecular polymer solution obtained in step (4), stirring and dispersing the mixture to obtain a coating solution; in the coating solution, the organic solvent accounts for 40% by weight, the high molecular polymer accounts for 13% by weight, the hydrophilic inorganic particles account for 40% by weight, the resin toughening agent accounts for 2% by weight, and the porogen accounts for 5% by weight;

[0070] (6) using a slot extrusion blade device to simultaneously apply the coating solution to both sides of the fiber substrate layer;

[0071] (7) The system obtained in step (6) in which both sides of the fiber substrate layer are coated with the coating solution is put into water for phase inversion, and after solidification, it is washed to obtain a diaphragm for hydrogen production by alkaline water electrolysis.

[0072] The finally prepared diaphragm for hydrogen production by alkaline water electrolysis includes a fiber substrate layer and a coating layer located on both sides of the fiber substrate layer. The thickness of the fiber substrate layer is 0.3 mm, and the total thickness of the diaphragm for hydrogen production by alkaline water electrolysis is 0.5 mm. A plurality of through-hole connection points are arranged on the fiber substrate layer, and the coating layers on both sides of the fiber substrate layer are connected into one body through the hole connection points. The cross-sectional shape of the hole connection point is circular. The area of ​​the hole connection point on the fiber substrate layer accounts for 56% of the total area of ​​the fiber substrate layer. The area of ​​a single hole connection point is 2.25 mm. 2 ; All porous connection points are evenly distributed on the fiber substrate, and the distance between any adjacent porous connection points is 0.5 mm; the diaphragm for hydrogen production by alkaline water electrolysis is placed in a NaOH solution with a constant temperature of 120°C and a mass concentration of 30% for one month, and the diaphragm for hydrogen production by alkaline water electrolysis loses weight by 0.25%; the diaphragm for hydrogen production by alkaline water electrolysis is subjected to a peeling test with the bonding material, and the diaphragm for hydrogen production by alkaline water electrolysis loses weight by 1% before and after the peeling test.

[0073] Example 2

[0074] A method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis, the specific steps are as follows:

[0075] (1) Preparation of raw materials:

[0076] Polyphenylene sulfide sulfone fiber;

[0077] Organic solvent: NMP;

[0078] High molecular weight polymer: polysulfone;

[0079] Porogen: PVP;

[0080] Hydrophilic inorganic particles: zirconium oxide;

[0081] Resin toughener: polybutadiene;

[0082] (2) using polyphenylene sulfide sulfone fiber as a raw material, a non-woven fabric structure substrate is prepared by a spunlace non-woven fabric process, wherein the non-woven fabric structure substrate is composed of short fibers with a length of 51 mm and a diameter of 15 μm;

[0083] (3) punching the non-woven fabric substrate in step (2) to obtain a fiber substrate layer;

[0084] (4) adding a high molecular weight polymer to an organic solvent and stirring until the high molecular weight polymer is completely dissolved to obtain a high molecular weight polymer solution;

[0085] (5) adding a porogen, hydrophilic inorganic particles and a resin toughening agent to the high molecular polymer solution obtained in step (4), stirring and dispersing the mixture to obtain a coating solution; in the coating solution, the organic solvent accounts for 60% by weight, the high molecular polymer accounts for 10% by weight, the hydrophilic inorganic particles account for 27% by weight, the resin toughening agent accounts for 1% by weight, and the porogen accounts for 2% by weight;

[0086] (6) using a slot extrusion blade device to simultaneously apply the coating solution to both sides of the fiber substrate layer;

[0087] (7) The system obtained in step (6) in which both sides of the fiber substrate layer are coated with the coating solution is put into water for phase inversion, and after solidification, it is washed to obtain a diaphragm for hydrogen production by alkaline water electrolysis.

[0088] The finally prepared diaphragm for hydrogen production by alkaline water electrolysis includes a fiber substrate layer and a coating layer located on both sides of the fiber substrate layer. The thickness of the fiber substrate layer is 0.3 mm, and the total thickness of the diaphragm for hydrogen production by alkaline water electrolysis is 0.5 mm. A plurality of through-hole connection points are arranged on the fiber substrate layer, and the coating layers on both sides of the fiber substrate layer are connected into one body through the hole connection points. The cross-sectional shape of the hole connection point is circular. The area of ​​the hole connection point on the fiber substrate layer accounts for 76% of the total area of ​​the fiber substrate layer. The area of ​​a single hole connection point is 3.06 mm. 2; All the porous connection points are evenly distributed on the fiber substrate, and the distance between any adjacent porous connection points is 0.25mm; the diaphragm for hydrogen production by alkaline water electrolysis is placed in a NaOH solution with a constant temperature of 120°C and a mass concentration of 30% for one month, and the diaphragm for hydrogen production by alkaline water electrolysis loses weight by 0.2%; the diaphragm for hydrogen production by alkaline water electrolysis is subjected to a peeling test with the adhesive material, and the diaphragm for hydrogen production by alkaline water electrolysis loses weight by 0.7% before and after the peeling test.

[0089] Example 3

[0090] A method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis, the specific steps are as follows:

[0091] (1) Preparation of raw materials:

[0092] Polyphenylene sulfide sulfone fiber;

[0093] Organic solvent: NMP;

[0094] High molecular weight polymer: polysulfone;

[0095] Porogen: PVP;

[0096] Hydrophilic inorganic particles: zirconium oxide;

[0097] Resin toughener: polybutadiene;

[0098] (2) using polyphenylene sulfide sulfone fiber as a raw material, a non-woven fabric structure substrate is prepared by a needle-punched non-woven fabric process, wherein the non-woven fabric structure substrate is composed of short fibers with a length of 38 mm and a diameter of 12 μm;

[0099] (3) punching the non-woven fabric substrate in step (2) to obtain a fiber substrate layer;

[0100] (4) adding a high molecular weight polymer to an organic solvent and stirring until the high molecular weight polymer is completely dissolved to obtain a high molecular weight polymer solution;

[0101] (5) adding a porogen, hydrophilic inorganic particles and a resin toughening agent to the high molecular polymer solution obtained in step (4), stirring and dispersing the mixture to obtain a coating solution; in the coating solution, the organic solvent accounts for 40% by weight, the high molecular polymer accounts for 13% by weight, the hydrophilic inorganic particles account for 40% by weight, the resin toughening agent accounts for 2% by weight, and the porogen accounts for 5% by weight;

[0102] (6) using a slot extrusion blade device to simultaneously apply the coating solution to both sides of the fiber substrate layer;

[0103] (7) The system obtained in step (6) in which both sides of the fiber substrate layer are coated with the coating solution is put into water for phase inversion, and after solidification, it is washed to obtain a diaphragm for hydrogen production by alkaline water electrolysis.

[0104] The finally prepared diaphragm for hydrogen production by alkaline water electrolysis includes a fiber substrate layer and a coating layer located on both sides of the fiber substrate layer. The thickness of the fiber substrate layer is 0.3 mm, and the total thickness of the diaphragm for hydrogen production by alkaline water electrolysis is 0.5 mm. A plurality of through-hole connection points are arranged on the fiber substrate layer, and the coating layers on both sides of the fiber substrate layer are connected into one body through the hole connection points. The cross-sectional shape of the hole connection point is circular. The area of ​​the hole connection point on the fiber substrate layer accounts for 56% of the total area of ​​the fiber substrate layer. The area of ​​a single hole connection point is 2.25 mm. 2 ; All the porous connection points are evenly distributed on the fiber substrate, and the distance between any adjacent porous connection points is 0.5 mm; the diaphragm for hydrogen production by alkaline water electrolysis is placed in a NaOH solution with a constant temperature of 120°C and a mass concentration of 30% for one month, and the weight of the diaphragm for hydrogen production by alkaline water electrolysis is reduced by 0.16%; the diaphragm for hydrogen production by alkaline water electrolysis is subjected to a peeling test with the adhesive material, and the weight of the diaphragm for hydrogen production by alkaline water electrolysis is reduced by 0.6% before and after the peeling test.

[0105] Example 4

[0106] A method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis, the specific steps are as follows:

[0107] (1) Preparation of raw materials:

[0108] Polyphenylene sulfide sulfone fiber;

[0109] Organic solvent: NMP;

[0110] High molecular weight polymer: polysulfone;

[0111] Porogen: PVP;

[0112] Hydrophilic inorganic particles: zirconium oxide;

[0113] Resin toughener: polybutadiene;

[0114] (2) using polyphenylene sulfide sulfone fiber as a raw material, a non-woven fabric structure substrate is prepared by a wet papermaking non-woven fabric process, wherein the non-woven fabric structure substrate is composed of short fibers with a length of 12 mm and a diameter of 12 μm;

[0115] (3) punching the non-woven fabric substrate in step (2) to obtain a fiber substrate layer;

[0116] (4) adding a high molecular weight polymer to an organic solvent and stirring until the high molecular weight polymer is completely dissolved to obtain a high molecular weight polymer solution;

[0117] (5) adding a porogen, hydrophilic inorganic particles and a resin toughening agent to the high molecular polymer solution obtained in step (4), stirring and dispersing the mixture to obtain a coating solution; in the coating solution, the organic solvent accounts for 40% by weight, the high molecular polymer accounts for 13% by weight, the hydrophilic inorganic particles account for 40% by weight, the resin toughening agent accounts for 2% by weight, and the porogen accounts for 5% by weight;

[0118] (6) using a slot extrusion blade device to simultaneously apply the coating solution to both sides of the fiber substrate layer;

[0119] (7) The system obtained in step (6) in which both sides of the fiber substrate layer are coated with the coating solution is put into water for phase inversion, and after solidification, it is washed to obtain a diaphragm for hydrogen production by alkaline water electrolysis.

[0120] The finally prepared diaphragm for hydrogen production by alkaline water electrolysis includes a fiber substrate layer and a coating layer located on both sides of the fiber substrate layer. The thickness of the fiber substrate layer is 0.15 mm, and the total thickness of the diaphragm for hydrogen production by alkaline water electrolysis is 0.35 mm. A plurality of through-hole connection points are arranged on the fiber substrate layer, and the coating layers on both sides of the fiber substrate layer are connected into one body through the hole connection points. The cross-sectional shape of the hole connection point is circular. The area of ​​the hole connection point on the fiber substrate layer accounts for 56% of the total area of ​​the fiber substrate layer. The area of ​​a single hole connection point is 2.25 mm. 2 ; All the porous connection points are evenly distributed on the fiber substrate, and the distance between any adjacent porous connection points is 0.5 mm; the diaphragm for hydrogen production by alkaline water electrolysis is placed in a NaOH solution with a constant temperature of 120°C and a mass concentration of 30% for one month, and the weight of the diaphragm for hydrogen production by alkaline water electrolysis is reduced by 0.3%; the diaphragm for hydrogen production by alkaline water electrolysis is subjected to a peeling test with the adhesive material, and the weight of the diaphragm for hydrogen production by alkaline water electrolysis is reduced by 0.8% before and after the peeling test.

[0121] Example 5

[0122] A method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis, the specific steps are as follows:

[0123] (1) Preparation of raw materials:

[0124] Polyphenylene sulfide sulfone fiber;

[0125] Polyphenylene sulfide fiber;

[0126] Organic solvent: NMP;

[0127] High molecular weight polymer: polysulfone;

[0128] Porogen: PVP;

[0129] Hydrophilic inorganic particles: zirconium oxide;

[0130] Resin toughener: polybutadiene;

[0131] (2) using a mixed fiber of polyphenylene sulfide sulfone and polyphenylene sulfide fiber in a mass ratio of 1:1 as a raw material, a non-woven fabric structure substrate is prepared by a spunlace non-woven fabric process, and the non-woven fabric structure substrate is composed of short fibers with a length of 51 mm and a diameter of 12 μm;

[0132] (3) punching the non-woven fabric substrate in step (2) to obtain a fiber substrate layer;

[0133] (4) adding a high molecular weight polymer to an organic solvent and stirring until the high molecular weight polymer is completely dissolved to obtain a high molecular weight polymer solution;

[0134] (5) adding a porogen, hydrophilic inorganic particles and a resin toughening agent to the high molecular polymer solution obtained in step (4), stirring and dispersing the mixture to obtain a coating solution; in the coating solution, the organic solvent accounts for 40% by weight, the high molecular polymer accounts for 13% by weight, the hydrophilic inorganic particles account for 40% by weight, the resin toughening agent accounts for 2% by weight, and the porogen accounts for 5% by weight;

[0135] (6) using a slot extrusion blade device to simultaneously apply the coating solution to both sides of the fiber substrate layer;

[0136] (7) The system obtained in step (6) in which both sides of the fiber substrate layer are coated with the coating solution is put into water for phase inversion, and after solidification, it is washed to obtain a diaphragm for hydrogen production by alkaline water electrolysis.

[0137] The finally prepared diaphragm for hydrogen production by alkaline water electrolysis includes a fiber substrate layer and a coating layer located on both sides of the fiber substrate layer. The thickness of the fiber substrate layer is 0.3 mm, and the total thickness of the diaphragm for hydrogen production by alkaline water electrolysis is 0.5 mm. A plurality of through-hole connection points are arranged on the fiber substrate layer, and the coating layers on both sides of the fiber substrate layer are connected into one body through the hole connection points. The cross-sectional shape of the hole connection point is circular. The area of ​​the hole connection point on the fiber substrate layer accounts for 56% of the total area of ​​the fiber substrate layer. The area of ​​a single hole connection point is 2.25 mm. 2 ; All the porous connection points are evenly distributed on the fiber substrate, and the distance between any adjacent porous connection points is 0.5 mm; the diaphragm for hydrogen production by alkaline water electrolysis is placed in a NaOH solution with a constant temperature of 120°C and a mass concentration of 30% for one month, and the weight of the diaphragm for hydrogen production by alkaline water electrolysis is reduced by 0.19%; the diaphragm for hydrogen production by alkaline water electrolysis is subjected to a peeling test with the bonding material, and the weight of the diaphragm for hydrogen production by alkaline water electrolysis is reduced by 0.85% before and after the peeling test.

[0138] Example 6

[0139] A method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis, the specific steps are as follows:

[0140] (1) Preparation of raw materials:

[0141] Polyphenylene sulfide sulfone fiber;

[0142] Polypropylene fiber;

[0143] Organic solvent: DMAC and DMF in a volume ratio of 1:1;

[0144] High molecular weight polymer: polyethersulfone;

[0145] Porogen: polyethylene glycol;

[0146] Hydrophilic inorganic particles: alumina;

[0147] Resin toughener: polybutadiene;

[0148] (2) using a mixed fiber of polyphenylene sulfide sulfone fiber and polypropylene fiber in a mass ratio of 1:1 as a raw material, a non-woven fabric structural substrate is prepared by a wet papermaking non-woven fabric process, and the non-woven fabric structural substrate is composed of short fibers with a length of 38 mm and a diameter of 8 μm;

[0149] (3) punching the non-woven fabric substrate in step (2) to obtain a fiber substrate layer;

[0150] (4) adding a high molecular weight polymer to an organic solvent and stirring until the high molecular weight polymer is completely dissolved to obtain a high molecular weight polymer solution;

[0151] (5) adding a porogen and hydrophilic inorganic particles to the high molecular polymer solution obtained in step (4), stirring and dispersing the mixture to obtain a coating solution; in the coating solution, the organic solvent accounts for 52% by weight, the high molecular polymer accounts for 23% by weight, the hydrophilic inorganic particles account for 23% by weight, and the porogen accounts for 4% by weight;

[0152] (6) using a double-sided comma blade device, the coating solution is simultaneously applied to both sides of the fiber substrate layer;

[0153] (7) The system obtained in step (6) in which both sides of the fiber substrate layer are coated with the coating solution is put into water for phase inversion, and after solidification, it is washed to obtain a diaphragm for hydrogen production by alkaline water electrolysis.

[0154] The finally prepared diaphragm for hydrogen production by alkaline water electrolysis includes a fiber substrate layer and a coating layer located on both sides of the fiber substrate layer. The thickness of the fiber substrate layer is 0.2 mm, and the total thickness of the diaphragm for hydrogen production by alkaline water electrolysis is 0.4 mm. A plurality of through-hole connection points are arranged on the fiber substrate layer, and the coating layers on both sides of the fiber substrate layer are connected into one body through the hole connection points. The cross-sectional shape of the hole connection point is square. The area of ​​the hole connection point on the fiber substrate layer accounts for 40% of the total area of ​​the fiber substrate layer. The area of ​​a single hole connection point is 1.0 mm. 2; All the porous connection points are evenly distributed on the fiber substrate, and the distance between any adjacent porous connection points is 0.3mm; the diaphragm for hydrogen production by alkaline water electrolysis is placed in a NaOH solution with a constant temperature of 120°C and a mass concentration of 30% for one month, and the weight of the diaphragm for hydrogen production by alkaline water electrolysis is reduced by 0.34%; the diaphragm for hydrogen production by alkaline water electrolysis is subjected to a peeling test with the adhesive material, and the weight of the diaphragm for hydrogen production by alkaline water electrolysis is reduced by 0.81% before and after the peeling test.

Claims

1. A diaphragm for producing hydrogen by alkaline water electrolysis, characterized in that: It comprises a fiber base material layer and coating layers located on both sides of the fiber base material layer; a plurality of through hole-shaped connecting points are arranged on the fiber base material layer, and the coating layers on both sides of the fiber base material layer are connected into one through the hole-shaped connecting points.

2. The diaphragm for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: The fiber base material layer is a non-woven fabric structure, and is composed of short fibers with a length of 10 to 76 mm, and a diameter of the short fibers is 0.1 to 20 μm.

3. A diaphragm for producing hydrogen by alkaline water electrolysis according to claim 2, characterized in that: The fibers in the fiber base material layer are polyphenylene sulfide sulfone fibers or mixed fibers of polyphenylene sulfide sulfone fibers and other fibers, and the other fibers are one or more of polyphenylene sulfide fibers, polytetrafluoroethylene fibers, polypropylene fibers, polyethylene fibers, polyetheretherketone fibers and cotton fibers.

4. The diaphragm for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: The area of ​​the hole-shaped connection points on the fiber base material layer accounts for 30 to 90% of the total area of ​​the fiber base material layer.

5. A diaphragm for producing hydrogen by alkaline water electrolysis according to claim 4, characterized in that: The area of ​​a single hole connection point is 0.5 to 4 mm 2 All the hole-shaped connection points are evenly distributed on the fiber substrate, and the distance between any adjacent hole-shaped connection points is greater than 0.2 mm.

6. The diaphragm for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: The cross-sectional shape of the hole-shaped connection point is one or more of a circle, a square, an angle and a star.

7. The diaphragm for producing hydrogen by alkaline water electrolysis according to claim 1, characterized in that: The diaphragm for hydrogen production by alkaline water electrolysis is placed in a NaOH solution with a constant temperature of 120°C and a mass concentration of 30% for one month, and the weight loss of the diaphragm for hydrogen production by alkaline water electrolysis does not exceed 0.5%; A peeling test was performed on the diaphragm for producing hydrogen by electrolysis of alkaline water and the bonding material. The weight loss of the diaphragm for producing hydrogen by electrolysis of alkaline water did not exceed 1% before and after the peeling test.

8. The method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis according to any one of claims 1 to 7, characterized in that The steps include: (1) Using polyphenylene sulfide sulfone fiber or a mixed fiber of polyphenylene sulfide sulfone fiber and other fibers as raw materials, a non-woven fabric structure substrate is prepared by a papermaking non-woven fabric process, a needle-punched non-woven fabric process, a spunlace non-woven fabric process, a spunbond non-woven fabric process or a melt-blown non-woven fabric process; (2) punching the non-woven fabric structure substrate in step (1) to obtain a fiber substrate layer; (3) adding a high molecular weight polymer to an organic solvent and stirring until the high molecular weight polymer is completely dissolved to obtain a high molecular weight polymer solution; (4) adding a porogen and hydrophilic inorganic particles to the high molecular polymer solution obtained in step (3), or further adding a resin toughening agent, and stirring and dispersing the mixture to obtain a coating solution; (5) using a slot extrusion scraper device or a double-sided comma scraper device to simultaneously apply the coating solution to both sides of the fiber substrate layer; (6) The system obtained in step (5) with the coating solution coated on both sides of the fiber substrate layer is put into water for phase inversion, and after solidification, it is washed to obtain a diaphragm for hydrogen production by alkaline water electrolysis.

9. The method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis according to claim 8, characterized in that: In step (3), the organic solvent is one or more of NMP, NEP, DMAC and DMF, and the high molecular polymer is one or more of polysulfone, polyethersulfone and polyphenylsulfone; In step (4), the porogen is one or more of PVP, polyethylene glycol, ethanol and n-butanol, the hydrophilic inorganic particles are one or more of zirconium oxide, aluminum oxide, magnesium oxide, yttrium oxide, cerium oxide and titanium oxide, and the resin toughening agent is polystyrene or polybutadiene.

10. The method for preparing a diaphragm for producing hydrogen by alkaline water electrolysis according to claim 8, characterized in that: In the coating solution, the mass proportion of organic solvent is 30-70%, the mass proportion of high molecular polymer is 8-30%, the mass proportion of hydrophilic inorganic particles is 20-60%, the mass proportion of resin toughening agent is 0-2%, and the mass proportion of porogen is 1-15%.

Citation Information

Patent Citations

  • Reinforced diaphragm for alkaline hydrolysis

    CN110869538B